2021
DOI: 10.1038/s41564-020-00844-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of trypanosome coat protein VSGsur and function in suramin resistance

Abstract: Suramin has been a primary early-stage treatment for African trypanosomiasis for nearly one hundred years. Recent studies revealed that trypanosome strains that express the Variant Surface Glycoprotein VSGsur possess heightened resistance to suramin. We show here that VSGsur binds tightly to suramin but other VSGs do not. By solving high-resolution crystal structures of VSGsur and VSG13, we also demonstrate that these VSGs define a structurally divergent subgroup of the coat proteins. The co-crystal structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Although the exact mechanism of resistance is unclear, drug internalization via the endocytic lysosomal pathway seems to be reduced [63]. Recent resolution of the tertiary structure of VSG sur by X-ray crystallography revealed that VSG sur binds to suramin, reducing the concentration of bioavailable drug entering the trypanosome cell [64]. Furthermore, newly produced VSG sur has been hypothesized to bind the imported suramin inside the endosome, and to be then trafficked to the cell surface, effectively removing the drug from cells [64].…”
Section: Drug Resistancementioning
confidence: 99%
“…Although the exact mechanism of resistance is unclear, drug internalization via the endocytic lysosomal pathway seems to be reduced [63]. Recent resolution of the tertiary structure of VSG sur by X-ray crystallography revealed that VSG sur binds to suramin, reducing the concentration of bioavailable drug entering the trypanosome cell [64]. Furthermore, newly produced VSG sur has been hypothesized to bind the imported suramin inside the endosome, and to be then trafficked to the cell surface, effectively removing the drug from cells [64].…”
Section: Drug Resistancementioning
confidence: 99%
“…Based on studies on the VSG N-terminal domain from the 1990s, VSGs were long thought to invariably form homodimers of very similar structure (Freymann et al, 1990;Blum et al, 1993) with a more recently solved VSG structure also showing very similar structural traits (Bartossek et al, 2017). Other recent findings, however, suggest that the members of the large VSG family are structurally more diverse than previously thought, with some believed to form trimers on the cell surface (Pinger et al, 2018;Umaer et al, 2021;Zeelen et al, 2021). VSG homodimers are attached to the plasma membrane via two GPI anchors, with each one covalently linked to the C-terminus of one monomer (Ferguson et al, 1988).…”
Section: Gpi-anchored Molecules In Mammalian Host Stagesmentioning
confidence: 99%
“…Chebulinic acid is ellagitannin, a plant polyphenol with anticancer activity [61]. Suramin is a bispolysulfonated naphthylurea used for treatment of trypanosomiasis [62] as well as an antineoplastic agent used as a chemosensitizer [63,64].…”
Section: Human Adp/atp Carriermentioning
confidence: 99%